Evaluasi Penyusunan Rencana Strategi (Renstra) Institut Agama Islam Diniyyah Pekanbaru Tahun 2019-2024 (Prosiding Keislaman dan Sains, 2025)
Evaluation of the preparation of the Strategic Plan is an effort made to improve the plan that has been implemented in a particular organization or group. The purpose of this study is to find out how the process of preparing the strategic plan at IAI Diniyyah Pekanbaru and the obstacles faced in preparing the strategic plan. The steps that the researcher carried out in this study were 4 stages, namely the preparation, preparation, assessment and determination stages. The results of the evaluation in the preparation of the strategic plan at IAI Diniyyah Pekanbaru still found obstacles in the preparation stage. In terms of human resources, the quality and quantity need to be improved. Coordination between the preparation of the strategic plan has not been well established. The existing data is also not accurate and has not been updated.
Keywords: Evaluation; Preparation of the Strategic Plan; Diniyyah